Global challenges in the risk assessment of nanomaterials: Relevance to South Africa - Mary Gulumian; Eileen Kuempel; Kai Savolainen (South African Journal of Science)
Internationally, there are efforts to develop standardised toxicity testing and risk assessmentmethods for engineered nanomaterials (ENMs). To this end, health risk assessments need tobe conducted on ENMs synthesised in South Africa. Country-specific risk characterisationrequires specific exposure assessments for those ENMs for which the likelihood exists foroccupational and environmental exposure in that country. A challenge in hazard identificationand risk assessment related to ENMs, regardless of country of origin, is that data on toxicity,carcinogenicity, pharmacokinetics, and occupational or environmental exposure are generallynot available for most ENMs. Although the mechanisms previously identified as importantin the toxicity and carcinogenicity of particles and fibres may be applicable, the possibilityexists that the unusual physicochemical properties of ENMs may give rise to unique, andas yet unidentified, adverse effects. Moreover, generalised exposure scenarios that considerthe life cycle of the agent have not been developed and are needed for the complete riskcharacterisation of ENMs. As health risk assessment is both resource and labour intensive, it isimperative to identify the aims of such an exercise prior to embarking on large-scale projects,to ensure that the data most useful for public health decision-making is provided. Identifyingpriorities in South Africa, in coordination with international efforts, can facilitate the effectiveuse of research efforts for risk assessment and risk management decision-making.